Perbedaan Literasi Pemahaman Keuangan Terhadap Mahasiswa Akuntansi dan Mahasiswa Manajemen - Lydia Octaviani; Kazia Laturette (Universitas Widyatama, 2019)
This research aims to analyze the differences in understanding of financial literacy in Accounting and Manajemen students in the 2015-2016 class, knowing the level of literacy held by students of the Accounting Study Program and students of the Management Study Program, and to analyze differences in the understanding of financial literacy to Accounting students and Manajemen students. This study uses a quantitative approach and is carried out on students of the Accounting and Manajemen Study Programs at Ciputra Surabaya University. Data were collected using a questionnaire to students of Accounting and Management in the 2015-2016 class, with a total population of 739 people. The sampling technique used was disproportionate stratified random sampling, with a total sample of 307 students. The scale used in this study is the Likert scale and nominal. Independent data analysis methods tests were carried out with the help of IBM SPSS 24. The results of this study indicate that there are differences in the financial literacy level of Accounting and Manajemen students. The level of understanding of financial literacy of IBM and accounting students at a moderate level with different score scores This difference includes every individual who has different competencies, financial management and financial management, and also seminars or training given to students from lecture activities. There is a difference in understanding of financial literacy between Manajemen and Accounting students.